2021
DOI: 10.1371/journal.pone.0258475
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the factors associated with the mental health of frontline healthcare workers during the COVID-19 pandemic in Cyprus

Abstract: Introduction The spread of COVID-19 into a global pandemic has negatively affected the mental health of frontline healthcare-workers. This study is a multi-centre, cross-sectional epidemiological study that uses nationwide data to assess the prevalence of stress, anxiety, depression and burnout among health care workers managing COVID-19 patients in Cyprus. The study also investigates the mechanism behind the manifestation of these pathologies, as to allow for the design of more effective protective measures. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 46 publications
(47 reference statements)
0
16
0
Order By: Relevance
“…As a result, people's physical and mental health is being tested, especially for hospital staff who are close to the patients and burdened with caring for and tackling the COVID-19 disease ( Greenberg et al, 2020 ; Salazar de Pablo et al, 2020 ). A combination of occupational and non-occupational risk factors such as insecurity, confinement measures, extensive media coverage, fear of contamination and workload under extreme pressure have profound adverse effects on the mental health of hospital staff ( Greenberg et al, 2020 ; Kapetanos et al, 2021 ; Saeed et al, 2021 ). Doctors and nurses have been hardest hit as they are at the epicenter of the pandemic and constantly providing healthcare services ( Greenberg et al, 2020 ; Lima et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, people's physical and mental health is being tested, especially for hospital staff who are close to the patients and burdened with caring for and tackling the COVID-19 disease ( Greenberg et al, 2020 ; Salazar de Pablo et al, 2020 ). A combination of occupational and non-occupational risk factors such as insecurity, confinement measures, extensive media coverage, fear of contamination and workload under extreme pressure have profound adverse effects on the mental health of hospital staff ( Greenberg et al, 2020 ; Kapetanos et al, 2021 ; Saeed et al, 2021 ). Doctors and nurses have been hardest hit as they are at the epicenter of the pandemic and constantly providing healthcare services ( Greenberg et al, 2020 ; Lima et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, several surveys have shown increased rates of anxiety, depression, stress, and other mental health issues in this high-risk population ( Alnazly et al, 2021 , Aly et al, 2021 , Jahrami et al, 2021a , Jahrami et al, 2021b , Kapetanos et al, 2021 , Salari et al, 2020a , Salari et al, 2020b ). In addition, growing evidence showed that hospital staff needed frequent and regular screening for such mental health symptoms and consistent support for them ( Brooks et al, 2019 ; Greenberg et al, 2020 ) in outbreak emergencies ( Chong et al, 2004 ; Lee et al, 2018 ; Zhao et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies on working hours among healthcare workers during the pandemic have shown that those working longer hours had alarming burnout and stress scores. In addition, longer hours are associated with prolonged contact with patients or samples, prolonged time of wearing PPE, sleep deprivation, and poor eating habits [ 3 , 7 , 8 ]. These psychological effects among healthcare workers can be exacerbated by multiple risk factors such as gender, medical condition, financial status, and occupational differences.…”
Section: Introductionmentioning
confidence: 99%
“…This positively changes followers' trust, values, and perceptions, leading to higher levels of performance and motivation. Transformational leadership has four components: (1) idealized influence occurs when transformational leaders try to gain followers' respect and trust by being a role model and following high ethical standards in the workplace; (2) inspirational motivation relates to the frequency with which transformational leaders motivate followers by providing values and a vision about the goals to be accomplished; (3) intellectual stimulation relates to the frequency with which transformational leaders encourage followers to think outside the box, and enhance their creativity and autonomy; and (4) individualized consideration relates to the frequency with which transformational leaders show their concern and support for followers' needs by genuinely listening to followers' aspirations and difficulties within and even outside the workplace. Given that transformational leaders demonstrate positive behaviors that stimulate intellectual capacity, cultivate relationships, and encourage competence and skills development, followers' attitudes toward their leader and their work, in addition to their personal motivation in executing their assigned tasks, tend to be positively affected.…”
Section: Theoretical Background and Literature Reviewmentioning
confidence: 99%
“…Chefs cook high-quality and delicious meals and waiters courteously serve the dishes to customers. Healthcare workers provide assistance to patients and/or people with medical conditions and respond quickly during emergency situations [1][2][3][4]. These occupations generally require a great deal of interaction with clients, customers, or patients in order to satisfy the requirements of the services.…”
Section: Introductionmentioning
confidence: 99%